A Complementary Architecture: Enhancing the experience of Maynardville Park through a responsive architecture - Shepherd, Matthew (School of Architecture, Planning and Geomatics, 2024)
This dissertation aims to preserve and enhance the existing narratives of Maynardville Park. The chosen site exhibits a long-established history of diverse social and cultural intricacies that all deserve careful consideration. The site presents a variety of layers within and around the park, outlining the scope of this inquiry to address the internal happenings and surrounding edges. The objective of this dissertation is to produce a type of responsive architecture that synergises with this particular context. The architectural intervention boarders the park and its urban edge and bridges these two conditions to create a more interactive space. Presenting itself with a variety of both significances and shortcomings, Maynardville Park guides the trains of thought for the theoretical, technological, and architectural positions. The proposed architectural response is meticulously tailored to the specific attributes of Maynardville Park, ensuring its relevance and timelessness. Responsive architecture, by its nature, necessitates a degree of flexibility and user agency, qualities that this design inquiry thoughtfully incorporates into its programming. It collages the various narratives to create a sense of harmony among them. In response to the physical characteristics of Maynardville, the architectural scheme develops a comprehensive urban and architectural strategy that forges multiple responsive edge conditions, designed to attract people to the site. The scheme creates a precedent for future development that addresses its context and initiates positive change for the site.